The level of prolactin in patient with CKD V stage, which are treated with hemodialysis - Dudar, I.; Savchuk, V.; Loboda, O.; Gonchar, Y.; Shifris, I.; Krot, V. (Ukrainian Journal of Nephrology and Dialysis, 2018)
The prevalence of hyperprolactinemia in patients treated with hemodialysis (HD) is 30-65%. Aim of our work was to investigate the prolactin (PL) level in patients treated with hemodialysis. Methods. An open prospective, non-randomized study it was involved 43 patients with CKD in the VD stage treated with hemodialysis. Criteria for inclusion of patients in the study were: informed consent of the patient to participate in the study, treatment of HD for more than three months, Kt / V> 1,2; vascular access - AV-fistula. The exclusion criteria were: refusal of the patient to participate in the study, liver cirrhosis, acute hepatitis B, C, hypothyroidism, acute coronary syndrome, stroke, pregnancy, patients with malignant neoplasms; those who systemically receive medications such as tricyclic antidepressants, monoamine oxidase inhibitors, reserpine, methyldopa, phenothiazine derivatives, antiemetic drugs (zocrama metoclopramide), dopamine synthesis inhibitors, and antipsychotics. All patients were evaluated for PL in serum. Results. Patients treated with HD have reported an elevated PL level in 32 (74%) patients. The level of serum PL in patients treated with HD was higher compared to the control group: 47.17 ± 32.4 versus 11.76 ± 4.33 ng/ml (p <0.001). The violation of the menstrual cycle was 85% in the group of women with elevated PL compared with 20% in women with normal PL (p <0,05). In groups of women and men with elevated PL level, the Hb level was significantly lower (p <0,05). It was established that the level of TL had a negative correlation with the level of Hb (r = -0,36; p = 0,02) and a positive correlation between the level of TL and CRP (r = 0,32; p = 0,03). Conclusions. The prevalence of hyperprolactinemia in our study was 74%. Violations of the menstrual cycle were significantly more common in women with hyperprolactinemia (85% vs. 20%). The increase in the concentration of PL has a negative correlation with the level of Hb and a positive correlation with the level of CRP, which suggests the involvement of PB in the processes of chronic inflammation